2005
DOI: 10.3109/13814780509178237
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence: A study among a group of Turkish women

Abstract: Reasons for continuing the abusive relationship and the effectiveness of the scarce support resources should be evaluated more seriously. The potential role of the primary healthcare provider in eliminating barriers for identification and assessment of domestic violence should not be forgotten. Otherwise, domestic violence will still remain a 'family matter', hidden and neglected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…Our findings are consistent with previous reports that marital discord is the most consistent marker of intimate partner violence [19]. Level of satisfaction and intimate partner violence may be causally related or they may both be effects of common underlying factors such as the intensity and quality of communication between husband and wife, polygamy, adultery, neglect and others [42,43]. Inquiry about marriage satisfaction could possibly be used as an entry point to discuss the more sensitive issue of intimate partner violence.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our findings are consistent with previous reports that marital discord is the most consistent marker of intimate partner violence [19]. Level of satisfaction and intimate partner violence may be causally related or they may both be effects of common underlying factors such as the intensity and quality of communication between husband and wife, polygamy, adultery, neglect and others [42,43]. Inquiry about marriage satisfaction could possibly be used as an entry point to discuss the more sensitive issue of intimate partner violence.…”
Section: Discussionsupporting
confidence: 82%
“…The reasons for intimate partner violence are strikingly similar to reasons reported in the literature and differences exist mainly in the relative magnitude of the reasons [14,20,26,39,42]. Although only 5% of the women in the survey attributed intimate partner violence to alcohol, participants in the focus groups reported that consumption of alcohol, mainly by men but also by women, was an important reason for intimate partner violence [19,26,37,40,42].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In some stu di es on do mes tic ma ri tal vi o len ce among Tur kish wo men, men's alco hol in ta ke was fo und as an im por tant fac tor for wi fe abu se. [16][17][18] Alt ho ugh fa mily in co me was not fo und as a pre dic tor of fa mily vi o len ce, the re sults men ti o ned abo ve are highly con sis tent with Far ring ston's fa mily stress the ory and Al len and Stra us' fa mily re sour ces the ory abo ut the ca u ses of fa mily vi o len ce. 19,20 Ge ne rally spe a king, the ma in pre mi se sha red by the se two the o ri es is that lack of re so ur ces in the family is one of the ma in trig gers of fa mily stress, and that the com bi na ti on of the se fac tors may be a signi fi cant pre dic tor of fa mily vi o len ce be si des cul tural tra di ti ons.…”
Section: Discussionmentioning
confidence: 99%